2016
DOI: 10.5603/cj.a2016.0003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transferring patients with ST-segment elevation myocardial infarction to percutaneous coronary intervention-capable hospitals on clinical outcomes

Abstract: Background: Primary percutaneous coronary intervention (PCI) is recommended for ST-segment elevation myocardial infarction (STEMI) patients (194 vs. 90 min, p < 0.001). The median door-toballoon time was significantly shorter in the transfer group vs. the direct-arrival group (75 vs. 91 min, p < 0.001). Total death and the composite of MACE were not significantly different during hospitalization (5.1 vs. 3.9%, p = 0.980; 5.4 vs. 4.8%, p = 0.435, respectively) and at 1-year (8.2 vs. 6.6%, p = 0.075; 13.7 vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(28 reference statements)
3
7
0
Order By: Relevance
“…Our results also mirror the non-inferior outcomes associated with inter-hospital transfer in other medical and surgical settings, including: traumatic brain injuries (23,24); acute surgical conditions (25); and percutaneous coronary intervention for STsegment elevation myocardial infarctions (26)(27)(28). However, in the case of the latter, there is some evidence to suggest improved outcomes for patients who undergo direct admission to a facility providing definitive care perhaps related to the importance of a short door-to-balloon time (29,30).…”
Section: Discussionsupporting
confidence: 71%
“…Our results also mirror the non-inferior outcomes associated with inter-hospital transfer in other medical and surgical settings, including: traumatic brain injuries (23,24); acute surgical conditions (25); and percutaneous coronary intervention for STsegment elevation myocardial infarctions (26)(27)(28). However, in the case of the latter, there is some evidence to suggest improved outcomes for patients who undergo direct admission to a facility providing definitive care perhaps related to the importance of a short door-to-balloon time (29,30).…”
Section: Discussionsupporting
confidence: 71%
“…According to Korea Acute Myocardial Infarction Registry (KAMIR) statistics, 60.9% of STEMI patients first visit hospitals where PCI is not available. 12 A similar trend has been detected internationally, and in general, about half of STEMI patients visit hospitals initially where PCI is not available. 22,23 The AHA recommends a D1-to-B time of less than 120 minutes from the initial visit to a non-PCI facility to a PCI after transfer.…”
Section: Discussionsupporting
confidence: 57%
“…In the case of a transferred STEMI patient, however, the results have not been not satisfactory. According to Korea Acute Myocardial Infarction Registry (KAMIR) statistics, 60.9% of STEMI patients first visit hospitals where PCI is not available [ 12 ]. A similar trend has been detected internationally, and in general, about half of STEMI patients visit hospitals initially where PCI is not available [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 14 had reported the DTB time of 79 min vs. 36 min for such patients. Kim et al have also described the time for transfer patient to be less than the direct ER-attending patients (75 vs. 91 min) 15 . DTB in transfer patients had been taken from the door entry in our hospital and not from the door entry of the first contact of the referral doctor or hospital.…”
Section: Discussionmentioning
confidence: 77%